2015
DOI: 10.1007/s00125-014-3488-1
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal outcome in type 1 diabetes patients with diabetic nephropathy during 1988–2011

Abstract: Aims/hypothesis Our aim was to analyse possible changes in the glycaemic control, BP, markers of renal function, and obstetric and perinatal outcomes of parturients with diabetic nephropathy during 1988-2011. Methods The most recent childbirth of 108 consecutive type 1 diabetes patients with diabetic nephropathy and a singleton pregnancy were studied. Two periods, 1988Two periods, -1999Two periods, and 2000Two periods, -2011 . Antihypertensive medication usage increased before pregnancy (34% vs 65%, p=0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 41 publications
3
24
0
8
Order By: Relevance
“…An older study by Diamond et al reported that White's classification predicted perinatal mortality in diabetic pregnancies [11]. Fetal macrosomia in White's classes B to R and pre-eclampsia and SGA infants in class F may have contributed to the high emergency Caesarean section rates across White's classes [17]. The low vaginal delivery rates in classes R and F are in agreement with reports from other centres [13,22,26,27].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…An older study by Diamond et al reported that White's classification predicted perinatal mortality in diabetic pregnancies [11]. Fetal macrosomia in White's classes B to R and pre-eclampsia and SGA infants in class F may have contributed to the high emergency Caesarean section rates across White's classes [17]. The low vaginal delivery rates in classes R and F are in agreement with reports from other centres [13,22,26,27].…”
Section: Discussionsupporting
confidence: 69%
“…Gestational hypertension was defined similarly, but without the presence of proteinuria. Pre-eclampsia in patients with diabetic nephropathy was defined as worsening of hypertension (≥15 mmHg increase in systolic and/or diastolic blood pressure) with a proteinuria level of ≥5 g/24 h after 20 gestational weeks [17].…”
Section: Monitoring Of Glycaemic Statusmentioning
confidence: 99%
“…The chance of women with diabetic nephropathy having a 'take home baby' is thus very high. Other studies have demonstrated that the risk of pregnancy-induced deterioration of diabetic nephropathy is low if women enter the pregnancy with a serum creatinine level <200 μmol/l [3], and only one woman received dialysis treatment in the present cohort of pregnant women [1].This paper provides further evidence that intensive antihypertensive treatment during pregnancy is probably beneficial in these vulnerable women. Preterm delivery before 32 weeks was seen in 21% of the cases in this cohort during 2000-2011, and preterm delivery before 37 weeks was very common (>70%), mainly due to severe hypertensive disorders.…”
supporting
confidence: 50%
“…The chance of women with diabetic nephropathy having a 'take home baby' is thus very high. Other studies have demonstrated that the risk of pregnancy-induced deterioration of diabetic nephropathy is low if women enter the pregnancy with a serum creatinine level <200 μmol/l [3], and only one woman received dialysis treatment in the present cohort of pregnant women [1].…”
mentioning
confidence: 98%
See 1 more Smart Citation